Therapeutic Potential of Centella asiatica and Its Triterpenes: A Review - Sun, Boju; Wu, Lili; Wu, You; Zhang, Chengfei; Qin, Lingling; Hayashi, Misa; Kudo, Maya; Gao, Ming; Liu, Tonghua (Frontiers in Pharmacology, 2020)
Centella asiatica (also known as Centella asiatica (L.) Urb. or Gotu kola) is a traditional Chinese medicine with extensive medicinal value, which is mainly used in Southeast Asian countries. This study aimed to summarize the effects of C. asiatica and its main components on neurological diseases, endocrine diseases, skin diseases, cardiovascular diseases, gastrointestinal diseases, immune diseases, and gynecological diseases, as well as potential molecular mechanisms, to study the pathological mechanism of these diseases based on the changes at the molecular level. The results showed that C. asiatica and its triterpenoids had extensive beneficial effects on neurological and skin diseases, which were confirmed through clinical studies. They exhibited mainly anti-inflammatory, anti-oxidative stress, anti-apoptotic effects, and improvement in mitochondrial function. However, further clinical studies are urgently required due to the low level of evidence and lack of patients.